Risk factors for and pregnancy outcomes after SARS‐CoV‐2 in pregnancy according to disease severity: A nationwide cohort study with validation of the SARS‐CoV‐2 diagnosis. (25th January 2023) - Aabakke, Anna J. M.; Petersen, Tanja G.; Wøjdemann, Karen; Ibsen, Mette H.; Jonsdottir, Fjola; Rønneberg, Elisabeth; Andersen, Charlotte S.; Hammer, Anne; Clausen, Tine D.; Milbak, Julie; Burmester, Lars; Zethner, Rikke; et al.
Abstract: Introduction: We identified risk factors and outcomes associated with SARS‐CoV‐2 infection in pregnancy in a universally tested population according to disease severity and validated information on SARS‐CoV‐2 during pregnancy in national health registers in Denmark. Material and methods: Cohort study using data from national registers and medical records including all pregnancies between March 1, 2020 and February 28, 2021. We compared women with a validated positive SARS‐CoV‐2 test during pregnancy with non‐infected pregnant women. Risk factors and pregnancy outcomes were assessed by Poisson and Cox regression models and stratified according to disease severity defined by hospital admission status and admission reason (COVID‐19 symptoms or other). Using medical record data on actual period of pregnancy, we calculated predictive values of the SARS‐CoV‐2 diagnosis in pregnancy in the registers. Results: SARS‐CoV‐2 infection was detected in 1819 (1.6%) of 111 185 pregnancies. Asthma was associated with infection (relative risk [RR] 1.63, 95% confidence interval [CI] 1.28–2.07). Risk factors for severe COVID‐19 disease requiring hospital admission were high body mass index (median ratio 1.06, 95% CI 1.04–1.09), asthma (RR 7.47, 95% CI 3.51–15.90) and gestational age at the time of infection (gestational age 28–36 vs < 22: RR 3.53, 95% CI 1.75–7.10). SARS‐CoV‐2‐infected women more frequently had hypertensive disorders in pregnancy (adjusted hazard ratio [aHR] 1.31, 95% CI 1.04–1.64), early pregnancy loss (aHR 1.37, 95% CI 1.00–1.88), preterm delivery before gestational age 28 (aHR 2.31, 95% CI 1.01–5.26), iatrogenically preterm delivery before gestational age 37 (aHR 1.49, 95% CI 1.01–2.19) and small‐for‐gestational age children (aHR 1.28, 95% CI 1.05–1.54). The associations were stronger among women admitted to hospital for any reason. The validity of the SARS‐CoV‐2 diagnosis in relation to pregnancy in the registers compared with medical records showed a negative predictive value of 99.9 (95% CI 99.9–100.0) and a positive predictive value of 82.1 (95% CI 80.4–83.7). Conclusions: Women infected with SARS‐CoV‐2 during pregnancy were at increased risk of hypertensive disorders in pregnancy, early pregnancy loss, preterm delivery and having children small for gestational age. The validity of Danish national registers was acceptable for identification of SARS‐CoV‐2 infection during pregnancy. Abstract : Women with SARS‐CoV‐2 infection in pregnancy had increased risk of hypertensive disorders in pregnancy, early pregnancy loss, preterm delivery and small‐for‐gestational age. The validity of the SARS‐CoV‐2 diagnosis in relation to pregnancy in the Danish national registers was acceptable.